El límite a la tasa de interés remuneratoria en el régimen comercial de Colombia: ¿Costo de transacción y barrera legal? - Delvasto P., Carlos Andrés (2023)
The purpose of this paper is to analyze whether maximum interest rates charged on business loans constitute tran saction costs and barriers to entry in Colombian markets. The article begins by evaluating the access to and depth of financial markets in Colombia. The author then examines the system of interest rates, paying particular attenti on to the concept of interest charged on a loan, and explaining four theories that posit the existence of interest rate ceilings in Colombian law. The article ends with an economic and legal analysis of the existence of maximum interest rates on commercial loans in Colombia.